Scapular reconstructions after resection for bone tumors: a single-institution experience and review of the literature - Biazzo, Alessio; De Paolis, Massimiliano; Donati, Davide Maria (Acta Biomedica Atenei Parmensis, 2018)
Scapulectomy and limb-salvage surgery are indicated for low and high-grade tumors of the scapula and soft-tissue sarcomas that secondary invade the bone. After total or partial scapulectomy there are 3 options of reconstruction: humeral suspension (flail shoulder), total endoprosthesis and massive bone allograft. Nowadays prosthesis and allograft reconstructions are the most used and humeral suspension is reserved only as salvage technique when no other surgery is possible. Several studies reported dislocations and wound infections as the most frequent complications of scapular prosthesis, account for 10-20%. Recently, in the attempt to prevent these complications, some authors have used homologous allografts to replace shoulder girdle after scapulectomy for bone tumors, avoiding common complications of scapular prosthesis. Scapular reconstruction following tumor resection is a safe procedure and can be performed with good functional, oncological and cosmetic results but in reference centres and by skill surgeons. In this paper we present three cases of scapular reconstructions following resections for scapular tumors (chondrosarcoma in all cases) performed in our Institute and we analyse the different options of reconstruction described in the current literature. The final message is to send these rare tumors to reference centres where a multidisciplinary team is able to treat these rare entities and where a group of skill oncology surgeons are able to plan this complex surgery.